AIAA Guidance, Navigation and Control Conference and Exhibit 2008
DOI: 10.2514/6.2008-6832
|View full text |Cite
|
Sign up to set email alerts
|

Handling Qualities Evaluation for Spacecraft Docking in Low Earth Orbit

Abstract: A new generation of spacecraft is now under development by NASA to replace the Space Shuttle and return astronauts to the Moon. These spacecraft will have a manual control capability for several mission tasks, and the ease and precision with which pilots can execute these tasks will have an important effect on mission risk and training costs. A simulation evaluated the handling qualities of a generic space vehicle based on dynamics similar to one of these spacecraft, NASA's Crew Exploration Vehicle, during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Because those results did not show a clear trend in terms of handling qualities, they are not presented here. However, they are available in an earlier paper [27].…”
Section: Experiments Matrixmentioning
confidence: 99%
“…Because those results did not show a clear trend in terms of handling qualities, they are not presented here. However, they are available in an earlier paper [27].…”
Section: Experiments Matrixmentioning
confidence: 99%
“…Manual docking of spacecraft is a challenging and critical maneuver during space missions (Eliseev & Rauschenbach, 1977; Ellis, 2000; Mueller, Bilimoria, & Frost, 2008). During the Russian MIR missions, Salnitski (2000; Salnitski, Dudukin, & Johannes, 2001) observed that lack of training for more than 60 days erodes performance (Johannes et al 2016) such that docking maneuver safety is jeopardized.…”
mentioning
confidence: 99%
“…The motion of both vehicles was modeled, including primary orbital mechanics effects, using the flight dynamics model described in Ref. 12. This section describes various aspects of the experiment design.…”
Section: Experiments Designmentioning
confidence: 99%
“…Preliminary studies of lunar landing 11 and Earth orbit docking have been conducted. 12,13 This paper reports a follow-on experiment investigating the effect of pilot tools on handling qualities for spacecraft docking in low Earth orbit; specifically, the attenuation of handling qualities degradation arising from translation -into-rotation coupling.…”
Section: Introductionmentioning
confidence: 99%